2017
DOI: 10.1155/2017/7351238
|View full text |Cite
|
Sign up to set email alerts
|

Tail Nerve Electrical Stimulation and Electro-Acupuncture Can Protect Spinal Motor Neurons and Alleviate Muscle Atrophy after Spinal Cord Transection in Rats

Abstract: Spinal cord injury (SCI) often results in death of spinal neurons and atrophy of muscles which they govern. Thus, following SCI, reorganizing the lumbar spinal sensorimotor pathways is crucial to alleviate muscle atrophy. Tail nerve electrical stimulation (TANES) has been shown to activate the central pattern generator (CPG) and improve the locomotion recovery of spinal contused rats. Electroacupuncture (EA) is a traditional Chinese medical practice which has been proven to have a neural protective effect. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 64 publications
0
29
0
Order By: Relevance
“…Activity-dependent plasticity occurs in the spinal cord throughout life and plays an important role in the acquisition and maintenance of motor skills and in the effects of spinal cord injury and other CNS disorders [32]. The phenomenon observed in this study may be associated with the activity-dependent plasticity promoted by TANES or TANES-induced locomotor training [13]. This finding further demonstrates that the temporary ability to step or walk induced by CPG activation triggered through the TANES could be transformed into permanent ability which was not completely controlled by brain and brainstem.…”
Section: Discussionmentioning
confidence: 58%
“…Activity-dependent plasticity occurs in the spinal cord throughout life and plays an important role in the acquisition and maintenance of motor skills and in the effects of spinal cord injury and other CNS disorders [32]. The phenomenon observed in this study may be associated with the activity-dependent plasticity promoted by TANES or TANES-induced locomotor training [13]. This finding further demonstrates that the temporary ability to step or walk induced by CPG activation triggered through the TANES could be transformed into permanent ability which was not completely controlled by brain and brainstem.…”
Section: Discussionmentioning
confidence: 58%
“…The functional change is supported by the existence of a circuit of neurons in the lumbar spinal cord called the central pattern generator(CPG) 53. It has been reported that electrical stimulation can increase the expression of NT‐3 in the lumbar motor neurons and alleviate the muscle atrophy in the hindlimb, which will allow for the new treatment strategy in the injured spinal cord 54. In accordance with our previous work,12 we have provided here with further evidence that supports the use of bioactive scaffold to reform central pattern‐generating circuitry of spinal interneurons in canines.…”
Section: Discussionmentioning
confidence: 99%
“…Electroacupuncture/electrostimulation is another treatment that has long been used in spinal cord injury therapy and has been shown to inhibit inflammation, promote the secretion of neurotrophic factors, and reduce secondary injuries [29,30] . Chen et al [31] performed electroacupuncture on rats with spinal cord injury and found that this treatment is effective to prevent oligodendrocyte apoptosis and to improve functional recovery after spinal cord injury.…”
Section: Treatmentsmentioning
confidence: 99%